Resilience and educational outcomes in Footprints in Time - Hidderley, L; Skelton, F; Neuendorf, A (My University, 2011)
The first three waves of parent and study child data will be explored in this presentation. It will look at Wave 3 outcome data for the child cohort: the Strengths and Difficulties Questionnaire (SDQ), Who Am I?, Renfrew and teacher rated literacy scores and examines what affects these scores. What can LSIC tell us about the experiences Indigenous children and parents with preschool and school? Initial analyses suggest that children in Wave 2 who had been to preschool in Wave 1 tended to score higher on measures of vocabulary and school readiness than children who had not been to preschool or childcare. Initial analyses also suggest most children in the study do like school, are not bullied and are attending every day. The first three waves of parent and study child data will be explored in this presentation which provides unique insights into the educational experiences of Indigenous children and parents. With parent or guardian permission Footprints in Time sends questionnaires to the teachers and carers of the children in the study. This presentation will also discuss some of the preliminary findings from the teachers’ surveys, such as: the strengths of the study children that teachers identify, how far teachers predict a child will go in their education and the kinds of Indigenous specific activities and training available within their schools.
Keywords: Education and Training -- School readiness; Culture -- Indigenous; Learning, education and training; Culture; Education and Training; Indigenous; School readiness; Learning, education and training